2018
DOI: 10.1111/pde.13734
|View full text |Cite
|
Sign up to set email alerts
|

Investigating skin age analysis to reduce tanning intentions among adolescents: A pilot study

Abstract: As skin cancer rates continue to rise, targeted efforts to reduce excessive exposure to ultraviolet radiation are crucial. Adolescents are a high‐risk population for intentional tanning; thus, we sought to determine whether the novel use of skin age analysis with ultraviolet (UV) photography would be an effective tool for reducing intentions to tan in adolescents with a calculated skin age (measured by complexion analysis software) that exceeds their actual age. Surveying 85 students in this study, skin age di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(8 reference statements)
2
0
0
Order By: Relevance
“…Nevertheless, our findings suggest that although skin cancer prevention may be of importance for video contest participants, as implicated by increased sunscreen use intention, the desire to have tanned skin persists. This is in concordance with recent studies that used individualized appearance-based approaches, such as ultraviolet photography and age-enhancing software to promote photoprotective behaviors [10,[19][20][21][22]. Thus, future studies evaluating experiential learning methods, such as the video contest described herein, in conjunction with an appearance-based model, may show promise with this population.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, our findings suggest that although skin cancer prevention may be of importance for video contest participants, as implicated by increased sunscreen use intention, the desire to have tanned skin persists. This is in concordance with recent studies that used individualized appearance-based approaches, such as ultraviolet photography and age-enhancing software to promote photoprotective behaviors [10,[19][20][21][22]. Thus, future studies evaluating experiential learning methods, such as the video contest described herein, in conjunction with an appearance-based model, may show promise with this population.…”
Section: Discussionsupporting
confidence: 89%
“…We and others have previously shown that sun-protective behaviors decrease as children age [8][9][10]. Our current study confirms the critical need for continued sun-protective interventions in Utah's adolescent population: two-thirds had at least one sunburn within the past 2 years and nearly half reported intentional outdoor tanning within the past 2 years.…”
Section: Discussionsupporting
confidence: 84%